A low-cost 2D WO3/Ni3S2 heterojunction for highly stable hydrogen evolution. (3rd November 2021) - Sun, Tongming; Zhong, Weiting; Zhang, Mengke; Tang, Yanfeng; Wang, Jin; Xu, Chen; Hu, Lanping; Wang, Minmin
Abstract : A WO3 /Ni3 S2  heterojunction electrode is developed, which exhibits higher electrical/ionic conductivity and catalytic activity and stability due to the specific cooperativity. It also shows high hydrogen evolution performance both at low and high current densities. Abstract : A transition metal-based nanohybrid has recently been demonstrated as an electrocatalyst which shows great potential in replacing commercial precious metal catalysts in hydrogen evolution reactions. Herein, a tungsten trioxide/nickel disulfide (WO3 /Ni3 S2 ) heterojunction is developed. Compared to the corresponding single-component, the as-developed heterojunction electrode exhibits higher electrical/ionic conductivity and catalytic activity and stability due to the specific cooperativity. As expected, the WO3 /Ni3 S2 electrode shows high hydrogen evolution performance both at low and high current densities. In addition, the as-developed electrode can work stably for a long time both at high and low current densities.